A Combination of Traditional and Modern in the Dramaturgy of Ettore Petrolini - Hambardzumyan, Ani (Bulletin of Yerevan University B: Philology, 2024)
The article examines a number of features of the activities of Ettore Petrolini, a famous figure in Italian drama and theater of the first half of the 20th century. He was the author who breathed new life into traditional Italian theater. An accomplished playwright and actor, Petrolini was able to combine the tradition of commedia dell'arte, the Italian folk theater of the late Middle Ages, with the techniques of avant-garde theater, creating a unique combination of past and present. The playwright, drawing on the tradition of dell'arte, created both real masked characters and new theatrical thinking characteristic of his time.The structure of the plays was new in Petrolini's dramaturgy. He refrained from deep psychological immersions, preferred a simple plot, and based the action on comic scenes. In this sense, for him, the literary text was a secondary factor in the performance; what was important was the artist’s performing skills, which included the skill of improvisation.In the 20th century, many talented playwrights, actors and directors were known in Armenian literature and theater, but performances on the Armenian stage were staged primarily on the basis of the classical tradition. The principles and techniques presented in the article, which were used by the Italian playwright, can also be useful to the Armenian theater, giving it freshness and modernity.
Keywords: Petrolini; commedia dell'arte; imporvisation; classical tradition; mask; slitamento; character; zanni; grotesque; Nero